Subwavelength structures for silicon photonics biosensing. (January 2019) - Wangüemert-Pérez, J. Gonzalo; Hadij-ElHouati, Abdelfettah; Sánchez-Postigo, Alejandro; Leuermann, Jonas; Xu, Dan-Xia; Cheben, Pavel; Ortega-Moñux, Alejandro; Halir, Robert; Molina-Fernández, Íñigo
Highlights: Subwavelength waveguides are very attractive for achieving high performance sensors. The standard 220 nm silicon-thickness is not optimal for sensing purposes. Coherent interferometric architectures enable unambiguous and low cost biosensors. In the mid infrared, subwavelength structures show a strong potential for sensing. Abstract: Silicon photonic biosensors hold the potential for highly accurate, yet low cost point-of-care devices. Maximizing the sensitivity of the sensing chips while reducing the complexity and cost of the read-out system is pivotal to realize this potential. Here we present an extensive analysis, both from a practical and a theoretical perspective, of current biosensors, and analyze how subwavelength structures can be exploited to enhance their sensitivity. This study is not restricted just to the near-infrared band as we also determine the sensing capabilities of the suspended silicon waveguides with subwavelength metamaterial cladding working in the mid-infrared range. These waveguides have been recently proposed to cover the full transparency window of silicon ( λ < ∼ 8.5 μm), where the fingerprint spectral region of many molecules takes place and so a plethora of evanescent field absorption-based applications will be developed in the near future.